IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) TERHADAP KELUARGA PENERIMA MANFAAT (KPM) DI KELURAHAN BONTODURI KECAMATAN TAMALATE KOTA MAKASSAR (Fakultas Dakwah dan Komunikasi, 2020)
This research was conducted to see how the implementation of the Non-Cash Food Assistance Program (BPNT) for Beneficiary Families (KPM) in Bontoduri Village, Tamalate District. The results of this study indicate that the implementation of the Non-Cash Food Assistance Program (BPNT) in the Bontoduri Sub-District of Tamalate has been running quite well and is right on target for the poor who are less able to meet their needs but to fulfil their monthly needs has not been felt sufficiently. The constraints experienced by beneficiary families include: 1) inaccurate targeting of food aid to beneficiary family accounts, 2) distance between beneficiary families and distant e-warong, 3) inconsistency in the distribution schedule for non-cash food aid, 4) the existence of problems with broken, broken, lost and blocked cards.